Chemotherapy after whole-brain radiotherapy: a prognostic factor for metastatic breast cancer - Fadoua Bouguerra; Safia Yahyaoui; Wael Kaabia; Semia Zarraa; Hela Hammami; Ghaiet El Fida Noubbigh; Rim Abidi; Chiraz Nasr (Journal of Palliative Care And Hospice, 2023)
Background and Aim Breast cancer is the second most common cause of brain metastases after lung cancer. However, the incidence of cerebral metastases from breast cancer has increased during the last years. The purpose of this study is to determine the prognostic value of chemotherapy after whole-brain radiotherapy for patients with brain metastases from breast cancer. Methods We analyzed retrospectively 63 records of patients diagnosed with brain metastases from breast cancer and treated in the radiotherapy department at the Salah Azaiz Institute of oncology over a 5-year period between 2007 and 2011. All patients received whole-brain radiotherapy. Only 4 patients had surgical resection of the metastases before radiotherapy and 36.5% of patients received systemic treatment after irradiation. Results Overall survival was 19% at 1-year and median survival was 4,5 months. Univariate analysis indicated that systemic treatment after irradiation was correlated significantly with longer survival. (p=0,046). Conclusion Determining prognostic factors might help optimize individual treatment for metastatic breast cancer. The results of our study suggest that chemotherapy is more effective on brain metastases after irradiation. This can be explained by the fragilization of the blood-brain barrier by radiation and subsequently a better passage of cytotoxic agents.
Keywords: Brain metastases